2012
DOI: 10.1021/nn301536n
|View full text |Cite
|
Sign up to set email alerts
|

Development of Iron-Doped Silicon Nanoparticles As Bimodal Imaging Agents

Abstract: We demonstrate the synthesis of water-soluble allylamine terminated Fe doped Si (SixFe) nanoparticles as bimodal agents for optical and magnetic imaging. The preparation involves the synthesis of a single source iron containing precursor, Na4Si4 with x% Fe (x = 1, 5, 10), and its subsequent reaction with NH4Br to produce hydrogen terminated SixFe nanoparticles. The hydrogen-capped nanoparticles are further terminated with allylamine via thermal hydrosilylation. Transmission electron microscopy (TEM) indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 63 publications
3
67
0
Order By: Relevance
“…Alamar Blue assay is an ideal approach to quantitatively measure proliferation and metabolic status of cells, especially for cells cultured in suspension (such as MEL cells used in the current study). 27,28 Similar to the results of cell number counting, the Alamar Blue assay suggested that the concentration of half maximal inhibition on cell viability was greater than 10 μg/mL ( Figure 5B, P < 0.01). In contrast to nAg, MEL cells are fairly vulnerable to Ag ions (in AgNO 3 ) at even very low concentrations (0.08 μg/mL), with significant reduction in cell viability in comparison to the control ( Figure 5C, P < 0.05), and cell viability was dramatically impaired by Ag ions at 1.2 μg/mL ( Figure 5C, P < 0.001).…”
Section: Resultssupporting
confidence: 71%
“…Alamar Blue assay is an ideal approach to quantitatively measure proliferation and metabolic status of cells, especially for cells cultured in suspension (such as MEL cells used in the current study). 27,28 Similar to the results of cell number counting, the Alamar Blue assay suggested that the concentration of half maximal inhibition on cell viability was greater than 10 μg/mL ( Figure 5B, P < 0.01). In contrast to nAg, MEL cells are fairly vulnerable to Ag ions (in AgNO 3 ) at even very low concentrations (0.08 μg/mL), with significant reduction in cell viability in comparison to the control ( Figure 5C, P < 0.05), and cell viability was dramatically impaired by Ag ions at 1.2 μg/mL ( Figure 5C, P < 0.001).…”
Section: Resultssupporting
confidence: 71%
“…6 Silicon nanoparticles were either surface oxidized to SiO x upon aging in airsaturated aqueous suspensions to yield SiO x -SiNPs and SiO x -Fe-SiNPs, or surface modified to obtain propylamine-terminated particles, PA-SiNPs and PA-Fe-SiNPs.…”
Section: Resultsmentioning
confidence: 99%
“…4 Further approaches involved the combination in a single particle of silicon semiconductor materials with iron oxides 5 and the synthesis of iron-doped silicon nanoparticles obtained from iron-doped sodium silicide precursors (xFe:Na 4 Si 4 ). 6 The latter authors reported an extreme loss of photoluminescence with increasing iron dopant concentrations in the initial mixture. 4 Herein, we investigate the effect of iron on the photoluminescence, singlet oxygen generation, and cytotoxicity towards rat glioma C6 cells of iron-containing SiNPs (FeSiNPs) in an attempt to further understand the potential use of these particles as optical sensors and therapeutic agents in biological systems.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The fluorescent quantum yields are 1.4% (before wash), 1.7% (first wash), 1.8% (second wash) and 2.0% (third wash). Singh et al [23] reported similar results with undoped SiNPs which exhibit higher fluorescent quantum yields than iron-doped SiNPs.…”
Section: Resultsmentioning
confidence: 59%